Contribution of International Trade in Import Export in Indonesia - Wina Aulia Rizka; Siska Octavianita Br Sembiring; Keren Dwi Wulandari; Khairani Alawiyah Matondang (Indonesian Journal of Advanced Research, 2023)
This study aims to analyze the contribution of international trade to exports and imports in Indonesia using a qualitative approach. Through qualitative research methods, the authors explore various factors and dynamics that affect exports and imports in Indonesia and analyze their impact on the national economy. This study uses a qualitative method using a literature study related to the contribution of international trade in exports and imports in Indonesia. The results of this study indicate that international trade has a large contribution to exports and imports in Indonesia, such as in the field of exports increasing export earnings, creating jobs, economic diversification, while in the field of imports, namely meeting domestic needs, technology transfer and increasing productivity, better consumer choices, wider.